2011
DOI: 10.1177/159101991101700112
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of a Vertebral Artery Aneurysm via Puncture of the Surgically Exposed Vertebral Artery

Abstract: We describe a case of subarachnoid hemorrhage due to a ruptured right vertebral artery (VA) aneurysm where endovascular therapy via a trans-femoral route was not feasible. Therefore we surgically exposed the VA and directly punctured it at the C4 level, followed by successful coil embolization. Direct access to the vertebral artery using an anterior surgical approach is an alternative in cases where the proximal side of the artery is occluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Of those, we acquired 112 reports with full text. Of the 112, 20 studies described the number of coils used and so were eligible for inclusion in the present study [2,3,[6][7][8][14][15][16][17][18][19][20][21]27,[32][33][34][35]38]. We performed a systematic review using the 20 studies, which comprised 33 cases.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…Of those, we acquired 112 reports with full text. Of the 112, 20 studies described the number of coils used and so were eligible for inclusion in the present study [2,3,[6][7][8][14][15][16][17][18][19][20][21]27,[32][33][34][35]38]. We performed a systematic review using the 20 studies, which comprised 33 cases.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…It is relatively convenient to expose the V1 segment, and the C4 transverse foramen can be used as the marker during separation. Oka et al 11 reported a patient with a ruptured RVA aneurysm. The aneurysm was successfully embolized by exposing and puncturing the vertebral artery at the level of the C4 vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…The reported complication rates related to percutaneous or direct access approaches range from 0% to 50%. [7][8][9][10][11][12][13] The major complications include hematoma, arteriovenous fistula, pseudoaneurysm, and thrombosis. However, the benefits of aneurysm obliteration and reduction of future rupture risk outweigh the potential risks of direct vertebral artery access.…”
Section: Discussionmentioning
confidence: 99%
“…The case reports reporting direct puncture typically describe percutaneous access. [7][8][9][10][11][12] Only one recent case series detailed 3 cases of direct surgical access to the V1 segment for basilar aneurysms. 13 The one unsuccessful coiling resulted from an inability to insert the sheath due to the angle of access to the V1 segment.…”
Section: Discussionmentioning
confidence: 99%